The first case of recurrent ultra late onset group B streptococcal sepsis in a 3-year-old child. (2017) - Hosoda, Ai; Gatayama, Ryohei; Moriyama, Shiori; Ishii, Noriyuki; Yamada, Kenichiro; Matsuzaki, Youhei; Shinjoh, Masayoshi
Abstract: Group B streptococcus (GBS) is a commonly recognized cause of sepsis and meningitis in neonatal and young infants. Invasive GBS infection is classified into early onset GBS disease (EOD, day 0–6), late onset GBS disease (LOD, day 7–89) and ultra late onset GBS disease (ULOD, after 3 months of age). ULOD is uncommon and recurrence is especially rare. We present the first recurrent case of ULOD GBS sepsis in 3-year-old girl with a past medical history of hydrops fetalis and thoracic congenital lymphatic dysplasia. The first episode presented as sepsis at 2 years 8 months of age. The second episode occurred as sepsis with encephalopathy at 3 years 1 months of age. During each episode, the patient was treated using intravenous antimicrobials and her condition improved. Serotype examination was not performed in the first episode, but GBS type V was serotyped in the second episode. ULOD over 1 year of age is quite rare and may recur.